Evaluating of IL-34 as a Biomarker for Asthma in Children: Findings from Dhi Qar Province, Iraq - Kadhim , Atyaf Ali; Mahmood , Thikra Abdullah (Medical Science Journal for Advance Research, 2024)
Objective: To investigate the possible role of interleukin-34 in development of asthma in children and determine its effectiveness as a biomarker for monitoring disease severity. Methods: the current study focused on asthmatic children who were admitted to the two hospitals in Dhi-Qar province: Muhammad Al-Moussawi Children’s Hospital, Bint Al-Huda Teaching Hospital for Women and Children. The period of study was placed between December 2023 to March 2024. Specifically included (85) asthmatic children’s patients, their ages ranged from 6 months to 6 years old. To compare the results with healthy control subjects (85) children of the same ages and sex as the patients were randomly selected from the local community and hospital. The concentration level of serum interleukin-34 was measured by Enzyme-linked immunosorbent assay (ELISA). Results: the present study revealed a striking difference in IL-34 concentrations between asthma patients and controls. Asthma patients exhibited significantly elevated IL-34 levels (409.4±114.7 pg/ml) compared to their healthy counterparts (307.6±56.43 pg/ml), with a p-value of <0.001.